The safety and Efficacy of Phacoemulsification in Diabetic Versus Non-Diabetic Patients: A Systematic Review and Meta-Analysis: Doi: 10.36351/pjo.v41i2.1958 - Made Chindy Dwiyanti Marheni Putri; Wahyuni, Indri; Utami, Dita Mega; Farid, Zafirah Mutiani; Kloping, Nabila Ananda (Pakistan Journal of Ophthalmology, 2025)
This review aims to compare the safety and efficacy of phacoemulsification cataract surgery between diabetic and non-diabetic patients, focusing on the differences in postoperative outcomes. RevMan 5.4 was used for data analysis. Eighteen studies were included consisting of 2233 cases. We found better best corrected visual acuity (BCVA) at first post-operative day in non-diabetic patients and a lower endothelial cell density (ECD) in diabetic patients at 1stweek and 3rdmonth. The central corneal thickness (CCT) was significantly thicker in diabetic group at 1stweek and 1stmonth postoperatively. The coefficient of variations (CV) was significantly higher and hexagonal cell percentage (HCP) was significantly lower in the diabetic group at 1stweek. HCP was significantly lower in at 1st and 3rdmonth postoperatively in diabetic group. No significant difference of central macular thickness (CMT) was found.Phacoemulsification has a greater impact on corneal endothelial damage and visual acuity in patients with diabetes mellitus (DM).